PENINGKATAN PEMBELAJARAN BAHASA INDONESIA MATERI DENAH SUATU TEMPAT DENGAN MENGGUNAKAN METODE PEMBELAJARAN INQUIRI PADA SISWA KELAS VIII.4 DI SMPN 18 PEKANBARU TAHUN 2017 - YULINAR, YULINAR (Komunitas Manajemen Kompetitif, 2018)
Abstract This study aims to determine the improvement of student learning outcomes on the subjects of Indonesia language on the material Plan A Place with Inquiri method of learning in class VIII.4 in Junior High School 18 Pekanbaru. This form of research is a classroom action research with as many as two rounds (Cycle). Each round is done with four stages of planning, implementation, observation and reflection. The subjects of this study are students of class VIII.4 in Junior High School 18 Pekanbaru with the total of 35 students consisting of 14 male students and 21 female students. The data obtained in the form of Indonesian language learning results obtained from test and observation sheet of teaching and learning activities. Data collection methods used include test, observation and documentation. From the results in the first cycle of student learning outcomes to 40% with inactive classification. While in the second cycle of students in learning results increased to 60% with a very active classification. This situation indicates that improvements in the learning process of Indonesian with Inquiri method of learning in Indonesian language subjects in grade VIII.4 students in Junior High School 18 Pekanbaru can be said to be fully successful. Keywords: Indonesian Language, Inquiri Learning Method, Plan